1990
DOI: 10.1128/jb.172.5.2642-2649.1990
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the glyoxylate bypass operon: cloning and characterization of iclR

Abstract: In Escherichia coli, expression of the glyoxylate bypass operon appears to be controlled, in part, by the product of icIR+. Mutations (17,19). This bypass is essential for growth on acetate, since it yields C4 acids while avoiding the net loss of the acetate carbons as carbon dioxide in the Krebs cycle (Fig. 1). After induction, the flow of isocitrate through the glyoxylate bypass is regulated, in part, by the phosphorylation of isocitrate dehydrogenase (IDH), the Krebs cycle enzyme that competes with isoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 44 publications
2
78
0
Order By: Relevance
“…In P. aeruginosa, aceA (PA2634) and glcB (PA0482, malate synthase) are present at different genomic locations (18), and our global genomic analysis demonstrated that this is also the case in many other species of bacteria. In E. coli, IclR negatively regulates the aceBAK operon and appears to be directly regulated by glyoxylate and pyruvate, which have been shown to bind to the C-terminal domain of IclR (39,40). IclR is also indirectly regulated by FadR, a fatty acid biosynthesis regulator (41).…”
Section: Discussionmentioning
confidence: 99%
“…In P. aeruginosa, aceA (PA2634) and glcB (PA0482, malate synthase) are present at different genomic locations (18), and our global genomic analysis demonstrated that this is also the case in many other species of bacteria. In E. coli, IclR negatively regulates the aceBAK operon and appears to be directly regulated by glyoxylate and pyruvate, which have been shown to bind to the C-terminal domain of IclR (39,40). IclR is also indirectly regulated by FadR, a fatty acid biosynthesis regulator (41).…”
Section: Discussionmentioning
confidence: 99%
“…We identified a clone containing this Clal fragment, designated XGLY 1, by probing an E. coli X genomic library with two hybridization probes, generated by amplification of portions of the aceB and iclR regions. Primers were designed by reference to the known sequences of these genes (Byrne et al, 1988;Sunnarborg et al, 1990), and the sequences were amplified using Taq DNA polymerase according to Saiki et al (1988). The smaller of the two ClaI-Hind I l l fragments derived from the hGLYl clone, which contains all of the coding region for the IclR protein, including its natural promoter, was subcloned into pBR322, giving plasmid pCHicl.…”
Section: Methodsmentioning
confidence: 99%
“…et al., 1988;Rieul et al, 1988), along with the nearby structural gene for an apparent repressor protein, iclR (Sunnarborg et al, 1990;Nkgre et al, 1991). It has been demonstrated that IclR protein expressed from the cloned iclR gene interacts specifically with a small operator-like region of DNA in the promoter region of the aceBAK operon (Cortay et al, 1991;Nkgre et al, 1991Nkgre et al, , 1992.…”
mentioning
confidence: 99%
“…Thus, expression of the glyoxylate bypass enzymes is regulated transcriptionally by the available carbon sources (43), but the mechanism by which this is achieved is not known, although Wendisch et al suggested the involvement of acetyl-coenzyme A as a signaling molecule (43). In Escherichia coli, the IclR repressor controls the regulation of the aceBAK operon (6,38) and hence bypasses expression. The expression of iclR is regulated by FadR, which is known to regulate the expression of genes involved in fatty acid metabolism.…”
mentioning
confidence: 99%